Development of Mathematics E-Book on Pythagorean Theorem Material - Intyassandy, Dyah Shinta Lintang; Destiniar, Destiniar; Septiati, Ety (Department of Mathematics Education, Faculty of Mathematics and Natural Sciences, UNY, 2022)
This study aims to determine the response and potential effects of using a mathematics e-book on the Pythagorean theorem material. The method used in the development of this ebook is ADDIE. The research data was obtained through student response questionnaires, and student learning outcomes test The subjects used were 15 grade VIII students of SMP Negeri 3 Mesuji Raya, Kab. Ogan Komering Ilir, South Sumatra. Based on the results of data analysis, student responses about practicality obtained the criteria of